SO2 Donors and Prodrugs, and Their Possible Applications: A Review - Wang, Wenyi; Wang, Binghe (Frontiers in Chemistry, 2018)
SO2 is widely recognized as an air pollutant and is a known cause of acid rain. At sufficiently high level, it also causes respiratory diseases. A much lesser known side of SO2 is its endogenous nature and possible physiological roles. There is mounting evidence that SO2 is produced during normal cellular metabolism and may possibly function as a signaling molecule in normal physiology. The latter aspect is still at the stage of being carefully examined as to the validity of classifying SO2 as a gasotransmitter with endogenous signaling roles. One difficulty in studying the biological and pharmacological roles of SO2 is the lack of adequate tools for its controllable and precise delivery. Traditional methods of using SO2 gas or mixed sulfite salts do not meet research need for several reasons. Therefore, there has been increasing attention on the need of developing SO2 donors or prodrugs that can be used as tools for the elucidation of SO2’s physiological roles, pharmacological effects, and possible mechanism(s) of action. In this review, we aim to review basic sulfur chemistry in the context of sulfur signaling and various chemical strategies used for designing SO2 donors. We will also discuss potential pharmacological applications of SO2 donors, lay out desirable features for such donors and possibly prodrugs, analyze existing problems, and give our thoughts on research needs.